The Impact of Enterprise Digital Capability on Supply Chain Digitalization—From the Perspective of Supply Chain Cooperation - Sijie Chen; Zhaobo Tang (Journal of Theoretical and Applied Electronic Commerce Research)
This paper explores in depth the mechanism of enterprise digital capability effects in supply chain digital development by reconstructing the supply chain cooperation capabilities (digital diffusion capability and digital collaborative capability). We use the questionnaire data covering 272 Chinese manufacturing enterprises and apply a structural equation model to test the hypothesis. The empirical result demonstrates that enterprise digital capability does not directly have a significant impact on supply chain digitalization, and the supply chain cooperation capabilities play a mediating role between an enterprise’s digital capability and supply chain digitalization. The results are robust as we thoroughly consider the direction of enterprise capabilities and verify the systematic requirements of supply chain digitalization and the high order of enterprise digital capability. These provide a theoretical basis for enterprises to promote the digital transformation of their supply chain through digital technology.